Effect of Organizational Culture on Employee Performance of MSMEs With Creativity And Motivation as Mediation Variables - Syarifah, Atik; Nabhan, Faqih (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The culture that continues to develop within the organization from year to year unknowingly has several performance gaps that can impact creativity and motivation. This study aims to determine the effect of organizational culture on employee performance of micro, small and medium enterprises in Klaten Regency with creativity and motivation as mediating variables. The method used in this study is quantitative, collecting data using a questionnaire distributed to the people of Klaten Regency. Samples were taken from as many as 150 respondents with an accidental sampling technique. The results of this study state that Organizational Culture has a significant positive effect on employee performance, Organizational Culture has a significant positive effect on Creativity, Creativity has a significant positive effect on Employee Performance, Organizational Culture has a significant positive effect on Motivation, Motivation has a significant positive effect on Employee Performance, Creativity can mediate Organisational Culture on Employee Performance, Motivation can mediate Organizational Culture on Employee Performance.